The Story of the Pagaruyung Royal Heir Family: Literary and Historical Relations in the Novel of Negeri Perempuan - Rosa, Silvia (OKARA: Jurnal Bahasa dan Sastra, 2020)
A literary work is woven over the various texts around it. One of the texts that cannot be ignored is the social, cultural, and historical texts. Literary works must take into account their relationship with other texts. This article aims to discuss the relationship of the novel of Negeri Perempuan with historical texts, mostly the photo-shaped text of the family collection of the royal heirs of Pagaruyung. This research data collected through literature studies. The research data unit is in the form of words, sentences, and paragraphs in the novel of Negeri Perempuan. Data analysis takes place intertextually. The study shows seven intertextual forms in the novel of Negeri Perempuan, namely existence, expansion, modification, transformation, conversion, defamiliarization, and demitification. The author used the seven intertextual forms to confirm the existence of the family of the heirs of the Pagaruyung kingdom. We conclude that foto Tangga Batu Berlumut is a historical text used by writers to weave novel. This finding is evidence that the relationship between history and literary works is indisputable. History can be recorded in literary works; instead, literary works can record a nation's civilization's history